Freshwater Perkinsea: diversity, ecology and genomic information. (17th December 2019) - Jobard, M; Wawrzyniak, I; Bronner, G; Marie, D; Vellet, A; Sime-Ngando, T; Debroas, D; Lepère, C
Abstract: Studies on freshwater Perkinsea are scarce compared to their marine counterparts; they are therefore not well ecologically characterized. In this study, we investigated the diversity, distribution and ecological role of Perkinsea in freshwater ecosystems. Our approach included (1) the phylogenetic analyses of near full-length SSU and LSU sequences of freshwater Perkinsea, (2) a meta-analysis of public Perkinsea 18S ribosomal RNA gene sequences available from the freshwater environments (25 lakes, 4 rivers), (3) microscopic observations of Perkinsea associated with planktonic communities and (4) single amplified genome analysis. Whereas Perkinsea appear to be rare in river ecosystems (85 reads), they are found in almost all of the lakes studied. However, their diversity does vary considerably between lakes (from 0 to 2 463 Operational Taxonomic Units (OTUs)). Phylogenetic analysis showed that the Parvilucifera/Dinovorax/Snorkelia and Perkinsus/Xcellia/Gadixcellia clades resulted from an initial speciation event. This second clade is further split into well-supported, monophyletic groups, including a clade dominated by freshwater representatives, which is further structured into three distinct subclades: freshwater clade 1, freshwater clade 2 and a freshwater and brackish clade. The Perkinsea Single Amplified Genome (SAG) as well as most of the abundant Operational Taxonomic Units (OTUs) fall into freshwater clade 2. The tyramide signal amplification-fluorescent in situ hybridization method showed an internal association between Perkinsea and the colonial phytoplankton Sphaerocystis . The Single Amplified Genome (SAG) annotation contained 698 genes and gene ontology terms could be assigned to 486 protein-coding genes. Although the number of genes appears to be low (10.6% of the entire gene set assessed by BUSCO), the analysis of the proteome revealed some putative secreted virulence factors. This study showed a large distribution of Perkinsea across lake ecosystems and potential parasitic association with phytoplankton. However, further investigations are needed for a better knowledge on the role of these microorganisms in freshwater ecosystems.